Land Price and Development, A Criticism to the Logic of Urbanization - a case study of urban space production in Timoteo, MG, Brazil - Bernardo Furtado (European Regional Science Association (ERSA), 2005)
This quick essay aims to demonstrate the fundamental importance of the cost of producing and managing urban space from a developing country perspective. It also indicates, based upon vast literature, that the price of urban investments end up to have an expelling trend to citizens away from the benefits which they cannot afford. This paradox suggests a vice cycle in which the more the City invests the more expensive it becomes to its citizens who, helplessly, move out into unserviced neighborhoods. This paper ends with some suggestions to the problem.
Keywords: 330